Analysis of the Influence of Service quality on Customer Satisfaction and Loyalty at Bank BCA in Surabaya - Fadia, Nevy; Rachmat, Basuki; Indrawati, Trisa (Tekmapro, 2025)
This study aims to anslyze the influence of service quality on customer satisfaction and loyalty at Bank BCA in Surabaya. Service quality is a crucial factor in the banking industry as it affects customer satisfaction, which ultimately impacts their loyalty. This research employs a quantitative method with data collection conducted to Bank BCA customers. The data analysis technique used is regression analysis with the assistance of statistical software. The result of the study indicate that service quality has a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction also has a positive and significant effect on customer loyalty. These findings suggest that the higher the service quality provided by Bank BCA, the higher the level of customer satisfaction, which in turn enhances their loyalty to the bank. Therefore, Bank BCA need to continuously improve its service quality to maintain customer satisfaction and loyalty. Keywords: corporate image, service quality, customer satisfaction, customer loyalty.